Pop-Up Book Media Development to Improve Early Childhood Language Skills - Nuril Aini; Edo Dwi Cahyo (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This research aims to develop pop-up book media as a learning tool that can improve the language skills of young children. The method used in this research is research and development (R&D) with a development model which includes analysis, design, development, implementation and evaluation stages. Data collected. The subjects of this research were group B early childhood children at the Perintis Rejo Asri Kindergarten. So the results of this research show that the indicator of achievement of children's language development is 92.5%, based on the results of material experts, it is 97.72% with very feasible criteria, according to the results of media expert validation, it is 71.66% with adequate criteria, and According to the results of the questionnaire, the teacher response was 100% with very feasible criteria. Based on evaluation results from media experts, material experts, teachers, and responses from children, this pop-up book was declared very suitable for use in language learning at Perintis Rejo Asri Kindergarten.